2021
DOI: 10.1002/anie.202114602
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐Responsive Jamming of Nanoparticle Dense Suspensions towards Macroscopic Liquid–Solid Switchable Materials

Abstract: Nanoparticle aggregation for constructing functional materials has shown enormous advantages in various applications. Most efforts focused on ordered nanoparticle aggregation for specific functions but were often limited to irreversible aggregation processes due to the thermodynamic equilibrium. Herein, we report a reversible disordered aggregation of SiO2‐PNIPAAm nanoparticles (SPNPs) through thermo‐responsive jamming, obtaining smart liquid–solid switchable materials. The smart materials can display a switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Tunable surface functionalization is critical for the processing, long‐term storage, applications of inorganic NPs [56–60] . Inorganic NPs can be functionalized with a variety of ligands, such as small molecules, [61] surfactants, [62] dendrimers, [63] polymers, [64] and biomolecules, by covalent or non‐covalent conjugation between inorganic NPs and ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Tunable surface functionalization is critical for the processing, long‐term storage, applications of inorganic NPs [56–60] . Inorganic NPs can be functionalized with a variety of ligands, such as small molecules, [61] surfactants, [62] dendrimers, [63] polymers, [64] and biomolecules, by covalent or non‐covalent conjugation between inorganic NPs and ligands.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] The addition of responsive nanofillers is an alternative approach because nanofillers significantly improve the mechanical strength during the hardening process, but the complex preparation method and easy agglomeration substantially limit their scalability and applicability. [15][16][17][18] Recently, inspired by thermostable proteins, researchers have synthesized an isovolumetric self-adaptive polymer to solve the poor controllability, long response time, and low response level. [19] Nevertheless, continuous processing of self-adaptive materials to fibers is difficult owing to the influence of viscosity, solubility, and molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a design usually leads to reduced modulus change amplitudes (generally <20 times) and the maximum moduli at the stiffened state are also low (<1 MPa). Grafting LCST‐type polymers on nanoparticles to thermally induce percolating reinforcing network or particle jamming may greatly enhance material's mechanical strength at the stiffened state, yet the complicated manufacturing and elaborate control over particle assemblies largely limit their extensive applications [4, 19] . As an alternative, Gong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting LCST-type polymers on nanoparticles to thermally induce percolating reinforcing network or particle jamming may greatly enhance material's mechanical strength at the stiffened state, yet the complicated manufacturing and elaborate control over particle assemblies largely limit their extensive applications. [4,19] As an alternative, Gong et al recently reported a simply prepared, thermal stiffening, and isochoric poly(acrylic acid) (PAA)/calcium acetate hydrogel which showed 1800 times Young's modulus enhancement ( � 350 times storage modulus change) as well as high storage modulus at the stiffened state ( � 35 MPa). [20] The thermal stiffening effect is believed to arise from the reduced permittivity of calcium acetate and enhanced interchain interactions at high temperatures, and has enabled a few fascinating applications like thermoactivated protection, [20] switchable lubrication, [2] and cold-induced shape recovery.…”
Section: Introductionmentioning
confidence: 99%